Helal gıda ürünlerinde pazarlama karması elemanları - Ünalan, Musa (My University, 2017)
Helal gıda pazarı ticari olarak artmakta ve İslam inancını benimsemiş Müslümanlar da helal gıda ürünlerine karşı yoğun bir talep göstermektedir. Helal piyasası; gıda ürünleri, gıda dışı ürünleri (eczacılık, kozmetik vb) ve hizmetler (lojistik, bankacılık ve turizm) olmak üzere üçe ayrılır. Bu çalışmada sadece helal gıda ürünlerinin pazarlama karması elemanları olan ürün, fiyat, tutundurma ve dağıtım kavramları üzerinden incelenmesi yapılmıştır. Ayrıca yerli ve yabancı literatür taraması yapılarak helal kavramı, helal gıda pazarı, pazarlama karması, helal gıda ürünleri ile pazarlama karması arasındaki ilişki de incelenmiştir. Bu konuda literatürde fazla sayıda çalışmaya rastlanılmamıştır. Bu bakımdan yaptığımız incelemenin literatüre katkısı olacağını düşünmekteyiz. Halal food industry has been growth in commercial and Muslim population who are showing increased demand for halal products. Halal industry has three components which can be listed as food products, non-food products (pharmacy, cosmetics etc.) and services (logistics, banking and tourism). This study examined to halal food products in order to marketing mix (product, price, place, promotion). Also, this paper provides a review of prior literature to introduce the theoretical background of studying halal, halal food products and the relation between halal food products and marketing mix. There are limited studies in this subject on literature. In this respect, we think that this study will contribute to the literature.

Halal food industry has been growth in commercial and Muslim population who are showing increased demand for halal products. Halal industry has three components which can be listed as food products, non-food products (pharmacy, cosmetics etc.) and services (logistics, banking and tourism). This study examined to halal food products in order to marketing mix (product, price, place, promotion). Also, this paper provides a review of prior literature to introduce the theoretical background of studying halal, halal food products and the relation between halal food products and marketing mix. There are limited studies in this subject on literature. In this respect, we think that this study will contribute to the literature.
The marketing mix on halal food products
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Helal gıda pazarı; Helal gıda ürünleri; Pazarlama karması; 4p; Halal food market; Halal food products; The marketing mix